2015
DOI: 10.1002/cjoc.201400861
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of (R)‐ and (S)‐3‐Methylheptanoic Acids

Abstract: Starting from chiral methyl molecules 3 and 4, both derived from (R)-4-methyl-δ-valerolactone, we have accomplished the synthesis of (R) and (S)-3-methylheptanoic acids. Our methods are amendable to the syntheses of a wide variety of chiral 3-methyl alkanoic acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…The results implied that the best synergist effect of SA-LDH/IFR occurred at relatively low SA-LDH content. The similar trend has also been found in other nano-sized particles/IFR system [40,41].…”
Section: Resultssupporting
confidence: 89%
“…The results implied that the best synergist effect of SA-LDH/IFR occurred at relatively low SA-LDH content. The similar trend has also been found in other nano-sized particles/IFR system [40,41].…”
Section: Resultssupporting
confidence: 89%
“…[61] Also in the case of phenols, the addition of a single explicit water molecule increased the slope from 0.50 to 0.88. [61] Zhang [62] showed that the improvement of the regression slopes required the inclusion of 1 to 2 water molecules to both the ionic and neutral species for carboxylic acids, phenols, and alcohols, while in the case of pyridines the best slope is obtained when explicit molecules are added only to the cations.…”
Section: Isodesmic Proton Exchange Reaction In Solution and Linear Rementioning
confidence: 99%
“…In order to solve these problems, this article first established the mathematical model with the pipe diameter, thermal shrinkage, elongation at break, and number of seams as control variables by using elastic mechanics method and composite piping design. [10][11][12] Second, in order to obtain the optimal technological conditions for the preparation of polyester-ramie nonwoven, response surface analysis was used to optimize the manufacturing process, [13,14] and to investigate the effects of mixing ratio, the fiber web quantification and the needle-punched density on the thermal shrinkage of polyester-ramie nonwoven and the elongation at break of polyester-ramie nonwoven lining material. [15] Finally, the mathematical model of pipe diameter combined with the optimal technological conditions, to predict the size of pipe diameter of lining material for damaged pipelines with different pipe diameters, thus providing theoretical basis for the design of pipe diameter and preparation of tubular nonwoven composites for the nonpressure sewage pipes.…”
Section: Introductionmentioning
confidence: 99%